Nitric oxide and abscisic acid regulate osmoprotective and antioxidative mechanisms related to water stress tolerance of grapevines - Pontin, Mariela (2021)
Fil: Pontin, Mariela. nstituto Nacional de Tecnología Agropecuaria. Estación Experimental Agropecuaria La Consulta; Argentina.